Impact of work-integrated learning and co-curricular activities on graduate labour force outcomes. Issue 3 (4th March 2023) - Jackson, Denise; Rowe, Anna
ABSTRACT: The explicit linking of institutional funding to in-curricular industry engagement and graduate employment affirms the strategic importance of enhancing graduate employability in Australia. Key strategies to enhance graduate employability and employment outcomes are work-integrated learning (WIL) (where students engage with industry as part of their formal learning and assessment) and co-curricular activities (e.g. volunteering, leadership/award, and mentoring programmes), which are facilitated by the university but not embedded into curricula. While WIL is widely recognised for enhancing different aspects of student employability, the impact of co-curricular activities is less well-known. Further, there is a lack of empirical analysis on the nuanced impact of different forms of WIL and co-curricular activities on graduate outcomes. This research sought to explore the impact of a range of WIL and co-curricular activities on labour force outcomes among new higher education graduates. Findings are informed by national survey data for 51, 883 domestic graduates of both coursework and research degrees in Australia. They point to a strong labour market advantage from work-based WIL for Bachelor graduates, while undergraduate participation in co-curricular activities appeared to have less effect on labour force outcomes. However, there were consistent, positive results for industry mentoring and leadership/award programmes for increasing the chances of securing full-time work and reducing the likelihood of perceived overqualification among Bachelor and postgraduate coursework graduates. Implications for stakeholders and practice are discussed, as well as directions for future research.